MUSLIM CONSUMER BEHAVIOR AND HALAL PRODUCT CONSUMPTION - Muhammad Turhan Yani; Sri Abidah Suryaningsih (al-Uqud : Journal of Islamic Economics, 2019)
The purpose of article writing is to find out the impact of modernization on lifestyle in some Muslim societies that have a tendency to ignore the parameters of religion (Islam) in terms of consuming a food / beverage, medicine, even cosmetics product. The research method used is library research. The result of the analysis is that anything consumed in an Islamic perspective has implications for mental health. this is where awareness is needed that when Allah SWT. has given signs about halal and haram for food or drink, so there is a wisdom behind the provisions of Allah. In the context of normative law in Indonesia, halal standardization has also been strengthened by the Law of the Republic of Indonesia Number 33 of 2014 concerning Guarantee of Halal Products as a whole to all levels of society. In addition, the Government has also formed a body called the Halal Product Guarantee Agency which has the duty to hold a Halal Product Guarantee. This shows that the Government is also very concerned about the needs of its citizens in meeting the consumption of all products with halal standards.